Effect of aquatic exercise on mental health, functional autonomy, and oxidative dysfunction in hypertensive adults. (18th August 2018) - Da Silva, Luciano Acordi; Menguer, Lorhan; Motta, Janaina; Dieke, Beatriz; Mariano, Sindianra; Tasca, Gladson; Zacaron, Rubya Pereira; Silveira, Paulo Cesar Lock; Aurino, Pinho Ricardo
ABSTRACT: The aquatic exercise is an effective non-pharmacological therapy for prevention and control of hypertension. The objective of the present study was to investigate the effect of aquatic exercise on mental health, functional autonomy, and oxidative dysfunction in hypertensive adults. Methodologically 29 adults (mean age 53 ± 7.5 years) were included in the study, and were randomly grouped as hypertensive ( n  = 16) and non-hypertensive ( n  = 13). Both groups underwent low-intensity aquatic exercise program for 12 weeks. Outcomes were evaluated at week 0 and 12. The values for the following parameters decreased in the hypertensive group post training: anxiety (−6.2 ± 2 score; 60%), Timed Up and Go test (−7.4 ± 0.3 sec; 30%), protein carbonylation (−0.15 ± 0.03 nmol/mg protein; 50%), nitric oxide (12.4 ± 6 nmol/mg protein; 62%), interleukin-6 (−27.6 ± 5.7 pg/mg protein; 46%), and tissue necrosis factor-alpha (−52.4 ± 3.8 pg/mg protein; 40%); however, the values of the following parameters increased before training: Berg score (56 ± 2; 7.8%), flexibility (27 ± 1 cm; 71%); glutathione (3.1 ± 1.3 nmol/mg protein; 138%), and superoxide dismutase (1.6 ± 0.4 nmol/mg; 166%). In conclusion, we suggest that low-intensity aquatic exercise program improved anxiety, functional autonomy, and oxidative dysfunction in hypertensive adults.